Mechanisms of Osteoarthritic Pain. Studies in Humans and Experimental Models - Eitner, Annett; Hofmann, Gunther O.; Schaible, Hans-Georg (Frontiers in Molecular Neuroscience, 2017)
Pain due to osteoarthritis (OA) is one of the most frequent causes of chronic pain. However, the mechanisms of OA pain are poorly understood. This review addresses the mechanisms which are thought to be involved in OA pain, derived from studies on pain mechanisms in humans and in experimental models of OA. Three areas will be considered, namely local processes in the joint associated with OA pain, neuronal mechanisms involved in OA pain, and general factors which influence OA pain. Except the cartilage all structures of the joints are innervated by nociceptors. Although the hallmark of OA is the degradation of the cartilage, OA joints show multiple structural alterations of cartilage, bone, and synovial tissue. In particular synovitis and bone marrow lesions have been proposed to determine OA pain whereas the contribution of the other pathologies to pain generation has been studied less. Concerning the peripheral neuronal mechanisms of OA pain, peripheral nociceptive sensitization was shown, and neuropathic mechanisms may be involved at some stages. Structural changes of joint innervation such as local loss and/or sprouting of nerve fibres were shown. In addition, central sensitization, reduction of descending inhibition, descending excitation, and cortical atrophies were observed in OA. The combination of different neuronal mechanisms may define the particular pain phenotype in an OA patient. Among mediators involved in OA pain, nerve growth factor (NGF) is in the focus because antibodies against NGF significantly reduce OA pain. Several studies show that neutralization of interleukin-1ß and TNF may reduce OA pain. Many patients with OA exhibit comorbidities such as obesity, low grade systemic inflammation, and diabetes mellitus. These comorbidities can significantly influence the course of OA, and pain research just began to study the significance of such factors in pain generation. In addition, psychologic and socioeconomic factors may aggravate OA pain, and in some cases genetic factors influencing OA pain were found. Considering the local factors in the joint, the neuronal processes and the comorbidities, a better definition of OA pain phenotypes may become possible. Studies are under way in order to improve OA and OA pain monitoring.